FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Linda Meganita; Halim Dedy Perdana; Santoso Tri Hananto; Hanung Triatmoko (EkBis: Jurnal Ekonomi dan Bisnis, 2017)
The purpose of this study is: 1) knowing the sequence of audit procedure which most often signed off by auditor 2) testing effect of external and internal factors on premature signed off of audit procedure. The sample of this study are auditors of the Audit Board of the Republic of Indonesia (BPK RI) in the head office and the representative office. Sampling technique used is convenience sampling. Survey method for this study by distributing questionare. Data analysis uses Friedman test and regression logistic analysis with significance level (α) 5%.Friedman test result indicates that there are sequence of priority of audit procedure tend to be signed off. The most audit procedure which often to be signed off is internal auditor judgment and audit procedure which seldom to be signed off is substantive test. Logistic regression test shows that audit risk, materiality, professional commitment, and locus of control affect premature sign off of audit procedure, meanwhile time budget pressure, time deadline pressure, and role overload do not affect premature sign off of audit procedure.